2017
DOI: 10.1016/j.cub.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A Descending Neuron Correlated with the Rapid Steering Maneuvers of Flying Drosophila

Abstract: Summary To navigate through the world, animals must stabilize their path against disturbances and change direction to avoid obstacles and to search for resources [1,2]. Locomotion is thus guided by sensory cues, but also depends on intrinsic processes, such as motivation and physiological state. Flies, for example, turn with the direction of large-field rotatory motion, an optomotor reflex that is thought to help them fly straight [3-5]. Occasionally, however, they execute fast turns, called body saccades, eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 35 publications
5
68
1
Order By: Relevance
“…Across stimulus intensities and spatial configurations, we found that turn dynamics reflected both mechanosensory and visual input; antennal stabilization experiments argue that these signals are integrated within the brain. Although integration of both modalities was visible in nearly every stimulus configuration we tested, unexpected turns also occurred in many of our experiments, suggesting that the integrative process on which we have focused must coexist with mechanisms to generate stochastic turns [7,29,30]. …”
Section: Discussionmentioning
confidence: 93%
“…Across stimulus intensities and spatial configurations, we found that turn dynamics reflected both mechanosensory and visual input; antennal stabilization experiments argue that these signals are integrated within the brain. Although integration of both modalities was visible in nearly every stimulus configuration we tested, unexpected turns also occurred in many of our experiments, suggesting that the integrative process on which we have focused must coexist with mechanisms to generate stochastic turns [7,29,30]. …”
Section: Discussionmentioning
confidence: 93%
“…One recent study has identified descending neurons whose activity correlates with spontaneous saccades [19]. At present it is unknown what neural center could provide the trigger for bar-fixation saccades.…”
Section: Discussionmentioning
confidence: 99%
“…Once a saccade is triggered, visual motion appears to play no role in modulating its dynamics [17, 18], suggesting that they are ballistic, all-or-none events. In tethered flight, flies generate saccades in the absence of any visual motion, suggesting that endogenous processes may also evoke saccades [10, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…NP0212 > Shi ts flies at 34°C continued to make some sharp turns during optomotor stimuli (see NP0212 > Shi ts example trace in Figure 4C). Such turns, whose rate seems to be increased by optomotor stimuli and which have been noted previously [3, 29, 45], represent a potentially different class of flight maneuver from those blocked in NP0212 > Shi ts flies.…”
Section: Discussionmentioning
confidence: 56%